Taxonomic note on Impatiens longipes (Balsaminaceae) and description of the new species I. pseudolongipes - Gogoi, Rajib; Sherpa, Norbu; Borah, Souravjyoti (Phytotaxa, 2020)
The taxonomic identity of the species Impatiens longipes Hook.f. & Thomson is discussed and a lectotype has been designated for the name. Impatiens pseudolongipes is described and illustrated as a new species.